IgG4-related mastitis managed without excision or steroid therapy - Hirokazu Matsushima; Masayuki Kikuchi; Rika Miyabe; Sota Yamaguchi; Hidenori Kita; Junko Kobayashi; Takashi Ando; Koji Atsuta; Takayoshi Soga; Tsunehiro Shintani (Surgical Case Reports)
Abstract IgG4-related mastitis is an extremely rare IgG4-related sclerosing disease involving the breast that must be differentiated from breast cancer. There is currently no consensus regarding the optimal treatment strategies. Here, we report a case of IgG4-related mastitis followed up without excision or steroid therapy. Although the association between IgG4-related mastitis and breast cancer remains unclear, regular follow-up imaging and measurement of serum concentrations of disease activity markers may allow for follow-up without excision or steroid therapy.